Rediscovery of the tree snail Bulimus appressus von Martens, 1867, with Bulimus perversus tener von Martens, 1867 placed as subspecies of Amphidromus palaceus (Mousson, 1848) (Gastropoda: Camaenidae) - Bunjamin Dharma; Irwan Wipranata (Jurnal Moluska Indonesia, 2023)
Bulimus appressus von Martens, 1867 was described without shell image with the type locality "Java". In 1890, Boettger placed it under the genus Amphidromus Albers, 1850 as Amphidromus appressus (Von Martens, 1867); then Fulton, 1896 placed it as a variety of Amphidromus palaceus (Mousson, 1848). This variety status was followed by Pilsbry, 1900; Van Benthem Jutting, 1950; and Laidlaw & Solem, 1961. It was allegedly extinct, until the second author rediscovered several specimens in Cipayung, Bogor, West Java in April 2022. The shape of the shell is elongated, the spire is slightly tapered, the aperture is small, monochrome yellow or white in colour, without varices, and the sutures are appressed; based on these characteristics this variety is placed as a subspecies of Amphidromus palaceus (Mousson, 1848) as Amphidromus palaceus appressus (von Martens, 1867). Three specimens are deposited in MZB, Cibinong, Bogor, Indonesia. It is compared to the nominate subspecies Amphidromus palaceus palaceus (Mousson, 1848) and to Amphidromus toncruzi Dharma, 2012 from the Philippines whose suture of the last whorl is appressed to the penultimate whorl for 1.5 mm. This paper also discusses Bulimus perversus tener von Martens, 1867 from Mount Gedeh (Gede), West Java (van Benthem Jutting, 1950); the shell is small, relatively thin with a slightly tapered spire, monochrome light yellow in colour, without varices. Herein also this taxon is placed as subspecies of Amphidromus palaceus (Mousson, 1848), that is Amphidromus palaceus tener (von Martens, 1867). Compared with the nominate subspecies that has medium shell thickness and slightly convex spire.